Modelo de reconversión de pozos de petróleo para la producción de energía geotérmica en el noroeste peruano - Hinostroza Vega, Enrique Gaudencio (2025)
This paper analyzes end-of-life oil wells by incorporating them into a repurposing model to assess geothermal heat recovery and its conversion into electric power. The objective is to extend their productive life and reduce the abandonment rate. Between 2015 and 2022, the abandonment rate in northwestern Peru increased from three to 29 wells per year. This trend poses potential environmental and economic challenges due to decommissioning costs. The model was applied to Block I, which contains 262 temporarily abandoned wells. From this population, a sample of 101 wells with available data was selected for analysis. The model successfully identified eight wells that demonstrated mechanical integrity and geothermal potential, each capable of generating 142.8 kW of heat and 9.6 W of electric power. The results confirm the model’s applicability by extending the productive life of the wells and producing an alternative type of energy, thereby reducing the abandonment rate by 8%.